Meningkatkan Hasil Belajar IPS Melalui Model Pembelajaran Kooperatif Tipe Snowball Throwing Siswa Kelas IV - Asri Asri (Universtas Negeri Makassar, 2022)
The purpose of this study was to study IPS learning outcomes through the Snowball Throwing Type Cooperative Learning Model for Class IV Semester II UPT SD Inpres Kading, Soppeng Riaja District, Barru Regency for the 2018/2019 Academic Year. The research method used is this type of research is classroom action research (CAR), which has two cycles, cycle I and cycle II. Cycle I has stages including: Planning, action, observation, and reflection. The conclusion in this research is that the Snowball Throwing type of cooperative learning model can improve social studies learning outcomes for Class IV UPT SD Inpres Kading. This absolute success occurred because of the implementation of the Snowball Throwing cooperative learning model, namely by using a lottery in distributing learning material to each group and using plastic balls as a medium used to attach questions made by each student.